Amylin: Localization, Effects on Cerebral Arteries and on Local Cerebral Blood Flow in the Cat - Lars Edvinsson; Peter J. Goadsby; Rolf Uddman (The Scientific World Journal)
Amylin and adrenomedullin are two peptides structurally related to calcitonin gene-related peptide (CGRP). We studied the occurrence of amylin in trigeminal ganglia and cerebral blood vessels of the cat with immunocytochemistry and evaluated the role of amylin and adrenomedullin in the cerebral circulation by in vitro and in vivo pharmacology. Immunocytochemistry revealed that numerous nerve cell bodies in the trigeminal ganglion contained CGRP immunoreactivity (-ir); some of these also expressed amylin-ir but none adrenomedullin-ir. There were numerous nerve fibres surrounding cerebral blood vessels that contained CGRP-ir. Occasional fibres contained amylin-ir while we observed no adrenomedullin-ir in the vessel walls. With RT-PCR and Real-TimePCR we revealed the presence of mRNA for calcitonin receptor-like receptor (CLRL) and receptor-activity-modifying proteins (RAMPs) in cat cerebral arteries. In vitro studies revealed that amylin, adrenomedullin, and CGRP relaxed ring segments of the cat middle cerebral artery. CGRP and amylin caused concentration-dependent relaxations at low concentrations of PGF2a-precontracted segment (with or without endothelium) whereas only at high concentration did adrenomedullin cause relaxation. CGRP8-37 blocked the CGRP and amylin induced relaxations in a parallel fashion. In vivo studies of amylin, adrenomedullin, and CGRP showed a brisk reproducible increase in local cerebral blood flow as examined using laser Doppler flowmetry applied to the cerebral cortex of the a-chloraloseanesthetized cat. The responses to amylin and CGRP were blocked by CGRP8-37. The studies suggest that there is a functional sub-set of amylin-containing trigeminal neurons which probably act via CGRP receptors.